Teorema Titik Tetap pada Pemetaan Kontraktif di Ruang bernorma-2 Standar - Salsabila Ammari; Muh Nur; Naimah Aris (Jurnal Matematika, Statistika dan Komputasi, 2021)
This paper discussed about the proof of the fixed point theorem on the standard 2-normed spaces by using completeness. The completeness of the standard 2-normed spaces is shown by defining a new norm. Two linear independent vectors on standard 2-normed spaces are used to define the new norm, namely  which has been shown to be equivalent to standard norm.